Hubungan Kadar Apolipoprotein B dengan Tingkat Keparahan Stroke Iskemik - Ridho Ahmad Jabbar; Syarif Indra; Dedi Sutia; Yuliarni Syafrita; Restu Susanti; Fanny Adhy Putri (Universitas Pahlawan Tuanku Tambusai, 2025)
Background: Stroke is a leading cause of disability and the second leading cause of death worldwide. Ischemic stroke occurs due to vascular occlusion that restricts blood supply to the brain. Apolipoprotein B (ApoB) is the main component of atherogenic lipoprotein particles, which plays a role in the pathogenesis of atherosclerosis. The NIHSS is recommended as a valid and accessible tool for assessing the severity of acute stroke. Although ApoB has been studied as a lipid biomarker, evidence regarding its association with the severity of ischemic stroke remains limited. Methods: This cross-sectional study included 72 ischemic stroke patients with onset <72 hours who were admitted to Dr. M. Djamil General Hospital, Padang, from February 2025 to July 2025. Data were collected through interviews, physical examinations, supporting investigations, and laboratory tests. ApoB levels were measured using the ELISA method, and stroke severity was assessed using the NIHSS. Data analysis was performed using SPSS version 30.0, with statistical significance set at p < 0.05. Results: The mean Apolipoprotein B level was 105.25 mg/dL. Based on NIHSS assessment, patients with moderate stroke severity accounted for 43.1%, followed by mild stroke (37.5%) and severe stroke (19.4%). Statistical analysis showed no significant association between Apolipoprotein B levels and ischemic stroke severity (p = 0.614). Conclusion: There was no association between Apolipoprotein B levels and ischemic stroke severity.